2022
DOI: 10.3390/biom12101328
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Phosphatidylethanolamine and Anti-Phosphatidylserine Antibodies—Association with Renal Involvement, Atherosclerosis, Cardiovascular Manifestations, Raynaud Phenomenon and Disease Activity in Polish Patients with Systemic Lupus Erythematosus

Abstract: Objective. To evaluate the association between anti-phosphatidylethanolamine (aPE) and anti-phosphatidylserine (aPS) antibodies and cardiovascular risk, organ involvement and disease activity in systemic lupus erythematosus (SLE) patients. Methods. We studied 93 SLE patients and 30 controls. We analyzed levels of anti-phospholipid antibodies, including aPS and aPE, the profiles of antinuclear, anti-neutrophil cytoplasmic (ANCA) and anti-endothelial antibodies, carotid intima-media thickness (cITM) and atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…PS-specific IgG has been detected in patients with SLE, APS and systemic sclerosis/scleroderma (SSc) [8,10,13,14]. Recent cohort studies have reported the existence of PS-specific IgG in severe COVID-19 patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PS-specific IgG has been detected in patients with SLE, APS and systemic sclerosis/scleroderma (SSc) [8,10,13,14]. Recent cohort studies have reported the existence of PS-specific IgG in severe COVID-19 patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most severe manifestations in SLE patients, LN is initiated by renal immune-complex deposition and lymphocytic infiltration [12]. In SLE patients, the levels of phosphatidylserine (PS)specific phospholipase A1 and anti-PS antibodies are elevated and involved in lupus progression with multiple immunomodulatory effects [13,14]. However, it is unclear which B-cell subsets produce anti-PS antibodies and whether anti-PS antibodies contribute to tissue damage and nephropathy during SLE development.…”
Section: Introductionmentioning
confidence: 99%
“…PS-speci c IgG has been detected in SLE, APS and SSc. 8,10,13,14 Recent cohort studies have reported the existence of PS-speci c IgG in severe COVID-19 patients. 6 The prevalence of the antiphospholipid antibodies (aPL) associates with thrombosis, complications of pregnancy, and neurologic disorders in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 In SLE patients, levels of phosphatidylserine (PS)-speci c phospholipase A1 and anti-PS antibodies are elevated and involved in lupus progression with multiple immunomodulatory effects. 13,14 However, it has been unclear which B cell subsets produce anti-PS antibodies and whether anti-PS antibodies contribute to tissue damage and nephropathy during SLE development.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of APL may be associated with thrombus formation, which can lead to thrombosis and thrombocytopenia. These antibodies are related to early atherosclerosis and correlate significantly with cIMT in clinical studies [40,[139][140][141]. A summary of impact of antibodies on endothelial dysfunction and atherogenesis in SLE is provided in Table 2.…”
Section: Antibodiesmentioning
confidence: 99%